أثر إستخدام تقنیات الحاسوب في زیادة معلومات الطلبة في إجراء تجربة السیطرة على سرعة محرك تیار مستمر عن طریق الفیض المغناطیسي (Journal of the College of Education for Women, 2019)
The aim of this research is to study the effect of using computertechniques to increase students information at the experimenting the speedcontrol of dc motor by the magnetic field.Simulation of the experiment has been used by implementing“Electronics Workbench” software.The random sample, included (30) second year electrical departmentstudents, divided into two groups , experimental and control with pre-test andpost-test .The results showed great advantages for the experimental groupthrough the use of computer program in the laboratory. The calculated (t) was(10.6) which was significant and showed statistical differences between theexperimental and control group.According to the results, using the simulation in electrical machineslaboratory experiments through “Electronics work bench ", had been enforcethe students learning. The researchers recommended to utilize thistechniques either as supporting program to the ordinary laboratory work oras self- learning method which provide the possibility to repeat theexperiment or / and validate its results.